Tracing syndrome-specific trajectories of attention across the lifespan. - Cornish, K; Scerif, G; Karmiloff-Smith, A (2007)
This paper maintains that studies of atypical attention targeting one particular age group are unlikely to be informative of syndrome-specific deficits and their developmental changes. We propose a new approach to the study of attentional deficits in genetic disorders, arguing for tracing cross-syndrome developmental trajectories from infancy through childhood to adulthood. Few studies have incorporated a developmental approach to determine whether the pattern of deficits and proficiencies remains constant across developmental time. Fewer still have included a cross-syndrome perspective to address these issues. Focusing on the cognitive domain of attention and its component parts, and using a cross-syndrome developmental perspective, the present set of studies compared the trajectories of different aspects of attention in three developmental disorders: Fragile X syndrome (FXS), Down syndrome (DS) and Williams syndrome (WS). Hitherto, these syndromes have all been reported as displaying serious "attentional deficits" above those expected in the general population. We predicted that, when one considers in greater detail subcomponent processes of attention, then ostensibly common difficulties do not necessarily emerge from common developmental pathways. We addressed this question with two studies. The first focused on inhibitory control, orienting and selective attention in infants and toddlers, and the second concentrated on selective attention, sustained attention and inhibitory control in mid-late childhood. The current results and their integration with earlier findings in adults point both to commonalities and to important syndrome-specific differences in attentional component processes, questioning whether profiles remain constant across developmental time.